Reconfiguration of Women's Environmental Lover (Configuration of Environmentalist Women) - Elly Prihasti; Wuriyani Wuriyani (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
The women's movement continues to grow but their struggles continuesly struggle in Domestic challenge, power and economy. They are considered unfit. Power also threatens in voicing the protection of the natural environment. The description of women's struggle is contained in the text of the Women's Batak Opera on the edge of the Lake by Lena Simanjuntak. This opera text restores the identity of women who are closer and care about the environment that is starting to break down, also to values that are starting to disappear. Inductive methods used range from general to general or general problems. The problem analysis starts from the presentation of evidence in the text which is then dialogue with the concept of ecofeminism. The results show that it is not easy for women to express a voice of concern for nature, even though it has been discourse in the context of their cultural history. Furthermore, due to cultural changes that prioritize the interests of individuals and humans from ecology. This is a strong reason for some women to resist changes in voicing and releasing the natural damage caused by human activities.